Information System Quality and Its Impact on Individual Users’ Benefit: Analysing the Role of Knowledge Enablers - Iman Sudirman; Rajesri Govindaraju; Andara Arie Pratiwi (Jurnal Teknik Industri, 2014)
With increasing competitive pressures, companies are trying to improve the quality of their processes and the work quality of their. This fact has triggered the companies to improve their information systems. Having made some investments in IT systems, those companies look for ways to gain benefits from their investments. The benefit from IS investment arise when the use of information system (IS) provides some positive impact to the organisation in terms of business impacts and individual impacts. Thus, investigating IS impact for individual user„s performance is very important. This study explores the effect of IS quality on individual benefits. The influence of six moderating variables related to knowledge enablers on the impact of IS quality on individual benefits was studied. The six moderating variables are: collaboration, trust, learning, centralisation, expertise, and formalisation. Data was collected using questionnaires distributed at two big private companies in Indonesia. Data processing was done with the help of SPSS software. After factor analysis, IS quality was split into two variables: Information quality and System and service quality. The study found that both the variables influence the perceived individual benefits significantly. The influence of information quality on individual benefit is positively moderated by expertise, learning, centralisation and formalisation. Finally, the influence of system and service quality on individual benefit is positively moderated by expertise and formalization.